KONFLIK SOSIAL KAWASAN INDUSTRI JABABEKA DALAM PERSPEKTIF KOMUNIKASI - Hamluddin Hamluddin; Sarwititi Sarwoprasodjo; Ninuk Purnaningsih (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2019)
This study examined a conflict between Jababeka Industrial Estate (KIJ) and peopleliving around it in Cikarang, Bekasi Regency, West Java Province. The present studyused a stakeholder analysis approach with a qualitative descriptive method. Thepresent study aimed to examine the causes of the conflict, existing problems, and thestrategy for conflict resolution in the perspective of communication. In-depthinterviews were conducted with some stakeholders such as industrial estatemanagement, society, village official, religious leaders, local government, regionalhouse of representatives, and the non-governmental organization (NGO) to obtain theresults. The results suggest varied problems such as poor communication, differentopinions, different interests, varied social systems, polluted environment, limitedsources of income, and so on as the impacts of industrial estate development seem tobe driving forces of the conflict. Generally, the conflict is between the management ofindustrial estate and people living around it. In addition, the conflict was identified asthe open and closed conflict which was varied from the weak until the strong level.